Member Perception of Cassava Farmer Group Performance in Sungai Buluh Utara Village, Batang Anai District, Padang Pariaman Regency - Iqbal, Muhammad; Arianti, Nyayu Neti; Yuliarso, M. Zulkarnain (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
This research was conducted from January to February 2022 in Buluh Utara Village, Batang Anai District, Padang Pariaman Regency. The aim was to analyze members' perceptions of the performance of cassava farmer group. The number of farmer group members in Sungai Buluh Utara Village is 119 cassava farmers who are from four farmer group, namely the Women Farmer Group (Kelompok Wanita Tani, KWT) of Kampung Apar, Kampung Apar, Maju Sepakat and Harapan Baru. The number of respondents was 54 people obtained by the Slovin formula and taken proportionally from each farmer group. The performance of farmer group assessed by members includes the role or function of farmer group as Learning Classes, Cooperation Forums and Production Units. Farmers' perceptions of the performance of farmer group were measured using a Likert scale and then grouped into three categories namely Not Good, Quite Good and Good. The results showed that most of the members (61.11%) gave the perception that the performance of the cassava farmer group as a Learning Class was in the good category, while for the Cooperation Forum r the majority (74.08) of the members rated it was less good and for the role as a Production Unit is also viewed as unfavorable by as many as 66.67% of members.